Gambaran Dampak Waktu Layar Terhadap Tidur Pada Remaja: Tinjauan Pelingkupan - Haninan Salma Dianah; Nunung Siti Sukaesih; Amanda Puspanditaning Sejati (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Screen time is time spent watching television, using a laptop or computer, watching videos, playing games and using devices. In Indonesia, 62.5% of teenagers use social media for more than eight hours per day. Sleep is a basic human need or the main need in Abraham Maslow's hierarchical theory. The aim of this research is to determine the impact of screen time activities on teenagers. The method used was a systematic literature review. Articles were searched using the PubMed, Cochrane and Google Scholar databases. Articles were selected using the PRISMA flow diagram and the quality of the articles was analyzed using JBI (Joint Base Integrated). With eligibility criteria, namely 70%